Euthanasia of patients with the chronic renal failure - Novaković, Milan, psihijatar (Array, 2009)
Abstract: This study deals with frequency and form of euthanasia in dialysis patients with chronic renal failure (CRF) in Bosnia and Herzegovina (B&H) within the period from 2000 to 2006. Of total number of 2700 patients on dialysis we examined n=753 of them. Examinees with the Balkan Endemic Nephropathy (BEN) (n=348) were in the first group, and the Control group was formed of patients with other diseases (n=405). In this study the following methods were used: adapted Questionnaire from the Renal Registry of B&H, Beck’s Anxiety Inventory (BAI), Hamilton’s Depression Rating Scale (HDRS) and Mini-Mental Scale of Estimation (MMSE). Age of the BEN group of patients ranged: 64.77 ± 8.86 and the control one 53.85 ± 3.60. Multivariate analysis for the BEN group with passive euthanasia was: 0.760 (95%, CI=0.590–0.710) (p=0.001) and for the active one was 0.450 (95%, CI=0.125–0.510 (p=0.001). Euthanasia is associated with the rural life and renal heredity, and psychological BAI scale-total, HDRS–total and MMSE–total. For the BEN group passive euthanasia is 3.75% as well as active 0.86%. The findings stressed that euthanasia of dialysis patients requires better nephrological–psychiatric control and social care in B&H as well as complete program for the CRF samples protection too